2016
DOI: 10.1021/acs.energyfuels.5b02448
|View full text |Cite
|
Sign up to set email alerts
|

Upgrade of Low-Concentration Oxygen-Bearing Coal Bed Methane by a Vacuum Pressure Swing Adsorption Process: Performance Study and Safety Analysis

Abstract: The recovery of methane from oxygen-bearing coal bed methane (CBM) (25% CH4/65% N2/10% O2) by vacuum pressure swing adsorption (VPSA) was studied systematically in this work. Nevertheless, it is difficult to implement systematic safety investigations of the process just by bench-scale experiments and pilot plants. Emphasis was placed on the construction of a new way to analyze process safety based on a developed explosive triangle theory that could be able to provide guidance for comprehensive safety evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…(e) Extended Langmuir adsorption isotherm pattern is applied to characterize the adsorption equilibrium behavior of the adsorbate onto adsorbent. The quantized equations concerning an adsorption fixed-bed model 36,37 are presented in Table 3, and the initial and boundary conditions 37 for the breakthrough and cycle operation are given in Table S1. Besides, the physical properties of the adsorbent bed are the same as the breakthrough experiment, and the involved transport model parameters are provided in Table 4 to achieve simulation runs.…”
Section: Methodsmentioning
confidence: 99%
“…(e) Extended Langmuir adsorption isotherm pattern is applied to characterize the adsorption equilibrium behavior of the adsorbate onto adsorbent. The quantized equations concerning an adsorption fixed-bed model 36,37 are presented in Table 3, and the initial and boundary conditions 37 for the breakthrough and cycle operation are given in Table S1. Besides, the physical properties of the adsorbent bed are the same as the breakthrough experiment, and the involved transport model parameters are provided in Table 4 to achieve simulation runs.…”
Section: Methodsmentioning
confidence: 99%
“…As the isotherm of nitrogen and oxygen on active carbon is almost the same [19], VAM can be considered as methane and nitrogen. In this study, the isotherms of methane and nitrogen at 298 K, 308 K and 318 K are shown in Figure 5.…”
Section: Adsorbent Analysesmentioning
confidence: 99%
“…Bae et al [22] also showed the same result, that the methane concentration increases with the desorption time, and the desorption gas was mostly air if the desorption time was very short desorption. On the other hand, methane's mass transfer coefficient is lower than nitrogen and oxygen, and methane desorbed slower than nitrogen and oxygen [15,19,35]. Thus, nitrogen and oxygen desorbed first, and the vacuum exhaust step can emit this part of the low methane concentration gas.…”
Section: Effect Of Vacuum Exhaust Process On Vacuum Pressure Swing Admentioning
confidence: 99%
“…Pressure swing adsorption is one of the main methods to separate and accumulate CH 4 from CBM . Adsorbent is the core of adsorption; the common adsorbents are activated carbons (AC), , metal–organic frameworks (MOFs) and activated carbon fibers (ACFs).…”
Section: Introductionmentioning
confidence: 99%
“…Pressure swing adsorption is one of the main methods to separate and accumulate CH 4 from CBM. 5 Adsorbent is the core of adsorption; the common adsorbents are activated carbons (AC), 6,7 metal−organic frameworks (MOFs) and activated carbon fibers (ACFs). Among them, AC is the most widely used adsorbent and more suitable for CH 4 separation and accumulation from low-concentration CBM in industry because of its low cost, stable property, and unique microporosity.…”
Section: Introductionmentioning
confidence: 99%